TINGKAT INTELEGENSI DAN PERAN ORANG TUA TERHADAP KETERAMPILAN MENULIS BAHASA INGGRIS - Nurul Badriyatul Muthoharoh (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
Abstrac. The aims of this research is to know the effect of intelegence and roles of parent towards english writing skill. The research method was survey method which the sample is 80 person. Using correlation and regression technique to connect the data of intelegence and roles of parent towards the data of english writing skill. The data collection use validated instruments, including IQ test, questionarries and the score that has been owned by lecturer by using normality, liniearity and multycolliearity test. Hypothesis results are: 1) there is significant influence intelegence and roles of parent jointly to english writing skill. It is evidenced by acquisition of Fo = 6,581 and sig. ) 0.002 < 0.05. 2) there is significant influence intelegence to english writing skill. It is evidenced by acquisition of t-test = 2.829 and sig. 0,006 < 0.05. 3) there is significant influence roles of parent to english writing skill. It is evidenced by acquisition of t- test = 2.506 and sig. 0.014 < 0.05. Keywords. Intelegence, roles of parent, writing skill